Keharusan Percepatan Reformasi Birokrasi - Achmad Zainuri (Buletin Al-Turas, 2005)
Reformation movement for last 7 years (1998-2005) hasn't given significant influence yet for bureaucracy reformation. Bureaucracy organization, as state apparatus, is still regarded as corrupt, complicated, un-efficient, slow, high cost spended, and un-professional in public service. Therefore, good governance demand makes citizen as a customer who has to be served well, including in determinning and controlling their services.